Characterization of fake news about the pandemic COVID-19 in Brazil - Giovanna de Oliveira Libório Dourado, Ana Karolina Silva Ribeiro de Oliveira, Julia Maria de Jesus Sousa, Isaura Danielli Borges de Sousa, Lílian Machado Vilarinho de Moraes (Revista de Enfermagem da UFPI)
DOI: https://doi.org/10.26694/reufpi.v9i0.11226